Pemesanan Paket Wisata Berbasis Web Pada PT. Zidni Silna Semarang Web-Based Tour Package Bookings In PT. Zidni Silna Semarang (Information Technology and Telematics, 2013)
Abstract   PT. Zidni Silna is a travel agents service provider in  Semarang.  To  obtain  detailed  information  about  the packages, the customer have come to the office or call the sales. The problems of this research is how to facilitate the customer to search for the  informations  and booking the package tours. This research aims to expand the market of PT.  Zidni  Silna  Semarang,  so  the  customer  inside  and outside of Semarang city, and overseas customer also can order the package tours. Analytical tools  used are DFD (Data Flow Diagram), ERD (Entity Relationship Diagram) and   Flowchart. The software used is   MacromediaDreamweaver 8. Analysis and design result's are expected to help and provide convenience for customers to booking the  package  tours.  And   simplify  in  management  the package tours  report's  to the leader. This package tour bookings website’s is intended as a convenience  offer for the customers. With this online bookings the customers no longer need to ask for details of  each package and also order which tour packages are about to be booked online.  Keywords:  Booking, Tour Packages, Macromedia Dreamweaver 8